STRATEGI BERTAHAN HIDUP PENARAIK PERAHU MOTOR DI KAMPUNG PINANG SEBATANG KECAMATAN TUALANG KABUPATEN SIAK - Husnia "; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Pinang village of Tualang Subdistrict of Siak District. Thepurpose of this study was to analyze the dynamics of the life of a motor boat puller in PinangSatu village, how the social capital of towing a motorboat, and how the strategy in survival. Thetheory used is the strategy of survival, social adaptation, and social capital. The analysis used inthe problem questioning in this research is qualitative with descriptive approach which is thenanalyzed based on the theory and presented in the narrative qualitatively, the data retrievaltechnique in this research is the porposive sampling where the number of informants in thisresearch is 5 people. From the results of the research in the field of motor boat pullers establishthree strategies in survival which is an active strategy by exploiting the potential of the familyby looking for a side job and include family members in work, passive strataegi by pressing theamount of expenditure or by frugality, then apply a network strategy that is with Establishrelationships with relatives or other relations. Further social capital that occurs among fellowtowing workers, owners with boat towing workers, towing boats with passengers, and towingworkers boat to the community around that is by applying social capital, economic capital, andcultural capital.Keywords: Towboat Motor Boat, Endurance Strategy, Social Capital